An integrated simulation platform for a quadcopter system with fuzzy-tuned PID controllers / Moayad Hani Yacoub Abu Rmilah - Moayad Hani Yacoub , Abu Rmilah (2016)
Quadcopters are powerful flying robots that are given great interest for their various emerging applications. A quadcopter is an under-actuated system that is naturally unstable and, hence, requires a robust controller to perform rotational and translational maneuvering with high stability. This thesis develops an integrated simulation platform with visualization capability for a quadrotor unmanned aerial vehicle (UAV). The nonlinear dynamic equations of motion for the six degrees of freedom of a quadcopter have been derived from the first principles. The quadcopter dynamical model has been stabilized by PID and fuzzy-tuned PID controllers in order to test and compare their performance. The simulation platform for the quadcopter was developed using MATLAB and Simulink and integrated with the FlightGear Flight simulator in order to visualize the quadcopter motion in real time. The simulation results have shown the effectiveness of the two proposed controllers during altitude, attitude and path tracking control. However, performance indicators of the time response curves for positions and attitude have shown that the fuzzy-tuned PID controller could stabilize the quadcopter more efficiently and provided a faster response and smaller overshoots. Fuzzy-tuned PID controllers have reduced the overshoot along the vertical axis from 10.6% to 4.25%. It enabled the quadcopter to strictly track the planned path with very small tracking errors and time delay. The response of this controller was leading the response of the conventional PID controller by 1.13s during path tracking. The developed simulation platform significantly reduces the time-consuming and intensive testing on expensive quadcopter prototypes and, hence, shortens the total development time and design cost. The simulation platform is a promising tool that is very useful for students and researchers who would like to study and analyze the performance of quadcopter systems.